Reliability and validity of the Turkish version of Scleroderma Skin Patient-Reported Outcome in patients with systemic sclerosis - Fulden Sari; Zilan Bazancir Apaydin; Hakan Apaydin; Mehmet Kayaalp; Abdulsamet Erden; Serdar Can Güven; Berkan Armağan; Ahmet Omma; Orhan Kucuksahin; Şükran Erten (Archives of Rheumatology, 2024)
Objectives: This study aimed to translate the Scleroderma Skin Patient-Reported Outcome (SSPRO) questionnaire to the Turkish (SSPRO-T) language and to assess its validity and reliability. Patients and methods: Fifty-four systemic sclerosis (SSc) patients (51 females, 3 males; mean age: 49.8±10.4 years; range, 22 to 65 years) participated in the reliability and validity analysis between October 2022 and December 2022. The translation and cross-cultural adaptation of the SSPRO-T was applied in accordance with the procedure described by the Beaton guidelines. The SSPRO-T, the Scleroderma Health Assessment Questionnaire (SHAQ), the Health Assessment Questionnaire Disability Index (HAQ-DI), Skindex-29, and patient global skin severity were conducted in all participants for construct validity. The SSPRO-T was retested to assess its reliability after seven days. Results: The SSPRO-T had a four-factor structure. The total SSPRO-T score and its subgroups correlated positively with SHAQ, HAQ-DI, Skindex-29, and patient global skin severity. The internal consistency and reliability were excellent in overall SSPRO-T and in the subgroups: physical effect, emotional effect, physical limitation, and social effect (Cronbach’s α=0.94, 0.80, 0.95, 0.93, and 0.84, respectively). The SSPRO-T had excellent test-retest reliability (r=0.91, p<0.001). In addition, no floor effect or ceiling effect was observed. Conclusion: The SSPRO-T questionnaire is a reliable and valid tool and can be used in research and clinical practice in Turkish patients with SSc.